Ramla : city of Muslim Palestine, 715-1917 : studies in history, archaeology and architecture - Petersen, Andrew; Pringle, Denys (Archaeopress Archaeology, 2021)
This book presents a comprehensive overview of the history, archaeology and architecture of the city of Ramla from the time of its foundation as the capital of Umayyad Palestine around 715 until the end of Ottoman rule in 1917.